Clinical negligence costs: taking action to safeguard NHS sustainability. (2nd March 2020) - Yau, Christopher Wai Hung; Leigh, Bertie; Liberati, Elisa; Punch, Daniel; Dixon-Woods, Mary; Draycott, Tim
Abstract : The NHS cannot afford to divert more and more money to litigation, and we need to tackle the problem at source. Tim Draycott and colleagues set out four principles to reduce avoidable harm